Predicting grade-tonnage characteristics of undiscovered mineralisation: application of the USGS Three-part Undiscovered Mineral Resource Assessment to the Sandstone Greenstone Belt of the Yilgarn Block, Western Australia. Issue 3 (2nd July 2020) - Davies, Rhys S.; Schodde, Richard; Sykes, John P.; Groves, David I.; Trench, Allan; Dentith, Michael
ABSTRACT: The United States Geological Survey (USGS) Three-part Undiscovered Mineral Resource Assessment provides a framework for estimating undiscovered mineral endowment. Previous studies that applied the Three-part Assessment to estimate the undiscovered orogenic gold endowment of the Sandstone Greenstone Belt, Western Australia, have relied upon dated or expert-derived grade-tonnage models. Here, several assessments are conducted using local grade-tonnage models, comprising known orogenic gold deposits within the entire Yilgarn Block and several individual terranes with contrasting lithosphere- to terrane-scale characteristics. These models are generated through comprehensive review of historical exploration, resource and production data. Based on these models, the Sandstone Greenstone Belt is estimated to contain significant undiscovered gold mineralisation, with a median total endowment of between 166 and 298 t gold, and mean of 167–319 t gold. Although these updated grade-tonnage models provide an approximately 80 per cent variation in predicted gold endowment, it is still evident that the belt remains an under-explored region within the Yilgarn Block, Western Australia.